Finger Vein Recognition System Work Process - Atul Panchal; Aafrin Manknojiya; Jeel Bhatt; Vivek Dave; Yash Goyani; Finny Sam, Kunal Surve (Revista Electronica de Veterinaria, 2024)
Finger vein identification is a biometric authentication method that shows great promise because of its distinct features, which include high accuracy, resilience, and non-invasiveness. This study offers a thorough analysis of the developments, approaches, and difficulties in the field of finger vein identification. An introduction of the fundamental ideas behind finger vein identification is given at the outset, along with information on the structure of finger veins and the imaging methods used to record vein patterns. It then goes into the many methods and algorithms used in finger vein identification systems for matching, classifying, and extracting features. The report also discusses new developments in finger vein identification technologies, including multimodal biometric systems that combine finger veins with other biometric modalities and deep learning-based techniques.The main difficulties that finger vein identification systems encounter are also covered in this work, including differences within the same class, environmental influences, and security issues. It also looks at possible uses for finger vein recognition in a variety of industries, including banking, healthcare, and access control. The study ends with some suggestions for future research and possible ways to get around some of the current problems to speed up the creation of more durable and trustworthy finger vein detection devices.